2018
DOI: 10.2196/mhealth.9409
|View full text |Cite
|
Sign up to set email alerts
|

Using Google Glass in Surgical Settings: Systematic Review

Abstract: BackgroundIn recent years, wearable devices have become increasingly attractive and the health care industry has been especially drawn to Google Glass because of its ability to serve as a head-mounted wearable device. The use of Google Glass in surgical settings is of particular interest due to the hands-free device potential to streamline workflow and maintain sterile conditions in an operating room environment.ObjectiveThe aim is to conduct a systematic evaluation of the literature on the feasibility and acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 52 publications
0
47
0
1
Order By: Relevance
“…Hierdurch verbesserte sich die Genauigkeit der Trokarplatzierung im Gegensatz zur Kontrollgruppe, die nicht unterstützt wurde, um 33 %. Ein weiterer vielversprechender Ansatz stellt der Einsatz von Smartglasses dar [21,22], bei dem der Nutzer Fotos und Videos über eine digital vernetzte Brille live im Operationssaal während der Operation sichten kann.…”
Section: Anwendungsgebiete Der Telemedizin Innerhalb Der Urologieunclassified
“…Hierdurch verbesserte sich die Genauigkeit der Trokarplatzierung im Gegensatz zur Kontrollgruppe, die nicht unterstützt wurde, um 33 %. Ein weiterer vielversprechender Ansatz stellt der Einsatz von Smartglasses dar [21,22], bei dem der Nutzer Fotos und Videos über eine digital vernetzte Brille live im Operationssaal während der Operation sichten kann.…”
Section: Anwendungsgebiete Der Telemedizin Innerhalb Der Urologieunclassified
“…It is a head-mounted device designed in the shape of a pair of eyeglasses with a 5.0-megapixel integrated camera; wireless connection; and the ability to take pictures, record a video, and call people with simple voice commands or manually by touching the frame. A small prism placed on the right side of the device allows a display of information to the user [ 1 - 3 ]. As a whole, the multitasking capabilities of the device provide users a comfortable and multifunctional virtual experience.…”
Section: Introductionmentioning
confidence: 99%
“…As a whole, the multitasking capabilities of the device provide users a comfortable and multifunctional virtual experience. Although these advantages have not fully met the needs of private consumers, its voice control, wireless transmission capabilities, integrated camera, and app customization have attracted the interest of commercial industries and professionals from various fields, including the health care [ 1 , 2 ]. In human medicine, Google Glass has been tested in many nonsurgical fields such as on-demand data visualization and real-time analysis [ 4 ], clinical simulations [ 5 ], management of diabetes [ 6 ], and pediatric cardiopulmonary resuscitation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has shown that video laryngoscopy performed by a number of methods can be useful for teaching endotracheal intubation (ETI) to learners at many levels of medical specialization [1]. However, these video laryngoscopes are expensive and provide images of an inconsistent quality [2].…”
Section: Introductionmentioning
confidence: 99%